EVIDENCE BASED LEARNING: AN ANALYSIS OF IMPACT OF REMEDIAL TEACHING ON CONCEPTUAL UNDERSTANDING - Thote, Prashant; S, Gowri (International Journal of Research -GRANTHAALAYAH, 2021)
The flow in using the language of Chemistry is an important tool for students. Chemical formula is not a descriptive tool but also a heuristic tool. Most of the Secondary School students face challenges with Chemical formula (naming and writing). Inappropriate use of symbolic representation is the most common problem faced by students in Grade nine. The objective of the present paper is to enable Grade nine students to name and write the formula of Chemical compounds correctly. It is an attempt to investigate the complications faced by the students in formative assessment to acquire intended learning outcomes. To enhance the conceptual understanding and intended learning outcomes small group remedial teaching with experiential learning activities and worksheets are used. Small group work is used as a strategy to improve the learning outcomes and conceptual understanding among the students of Grade nine. The present study is limited to the students of one school and one unit of Science. Totally 40 students participate in the study. Sample students are divided into two group study group and control group equally on the basis of their previous knowledge of the subject. Students of study group are taught by using small group remedial experiential activity. The present study is experimental in nature. Data is analyzed by using mean, mean difference and standard deviation. The vital variance between the mean score of both groups on variables of pre-formative assessment and post-formative assessment score is tested at 0.05 level by applying t-test. The result of the present study reveals that there is a significant positive impact of small group remedial teaching on conceptual understanding of naming and writing the Chemical formulae of Chemical compound in Science subject among the students of Grade nine. Based on the result of the study teachers must provide small group remedial teaching to the students facing challenges in conceptual understanding to acquire the intended learning outcomes.